Padrões de crescimento e desenvolvimento de larvas de catorze espécies de anuros em diferentes ambientes do cerrado: as estratégias são semelhantes? - Fonseca, Guilherme Albertino (2022)
Brazil is home to the greatest wealth of anurans on the planet, of which 209 species occur in the Cerrado. This biome has a high heterogeneity of habitats due to its two well-defined seasons, rainy and dry. This seasonality offers different habitat conditions and reproduction conditions for amphibians, which have a biphasic life cycle, in which most species have aquatic larvae and terrestrial adults. Heterochrony is a phenomenon that occurs with several groups of organisms and with frog larvae, referring to morphological changes over time of ontogenetic development of frogs in relation to their ancestors. This pattern of development can be described with developmental tables, which make it possible to describe the ontogenetic sequences of different species. Growth curves help to describe and predict the growth rates of animals by summarizing some parameters as growth characteristics of organisms. In this work we explore how the patterns of growth and development of tadpoles occur in 14 anuran species from the cerrado that use temporary or perennial environments for larval development. For this, we sought to explore the difference in the growth rate of tadpoles of different species that occur between temporary and perennial environments, and the differences in the investment in body growth, expressed in the difference in size between individuals in the earlier and later larval stages, between species that reproduce in these different environments. We expect that in perennial environments the larvae show greater growth in initial size and grow a little during the late stages of metamorphosis. In seasonal environments, we expect tadpoles to present faster development and lower larval growth, presenting metamorphosis in a short time interval and with smaller images. However, we found no differences in developmental strategies among the 14 species, which may be related to habitat use. In general, the species followed the growth. The species Bokermannohyla pseudopseudis showed a more differentiated growth curve among the studied species, which may be related to its way of life and relationship with the development environment, thus seeking the need for further studies regarding its ontogeny in relation to its reproduction environment. The study of growth curves can be a promising approach for understanding the understanding and communities of amphibians in the Cerrado.